DINAMIKA SENTRA INDUSTRI KECIL MENUJU ERA PERDAGANGAN BEBAS - Farid Wajdi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2005)
The most of small-scale industry in Indonesia is at a center community. The activities of theentrepreneur of small scale industrial if seen from pattern link of its job environmentally its businessown is difference of among one small entrepreneur with other. Based on the difference pattern of its linkhence the small entrepreneur can be grouped into mains entrepreneur, entrepreneur of free entrepreneurand follower. The main entrepreneur is important position, which can determine to succeed in thereassignment of small industry at one particular of a center community. Therefore, to evaluate thereadiness of small industry in face of free trade era hence attention and target of development shall beaddressed to mains entrepreneur.